2019
DOI: 10.1080/13875868.2019.1569016
|View full text |Cite
|
Sign up to set email alerts
|

The acquisition of survey knowledge for local and global landmark configurations under time pressure

Abstract: The influence of stress states on cognition is widely recognized. However, the manner in which stress affects survey knowledge acquisition is still unresolved. For the present study, we investigated whether survey knowledge acquisition during a stressful task (i.e., under time pressure) is more accurate for the mental representation of global or local landmarks. Participants navigated through virtual cities with a navigation aid and explicit learning instructions for different landmark configurations. Particip… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
12
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
7
1
1

Relationship

0
9

Authors

Journals

citations
Cited by 20 publications
(12 citation statements)
references
References 83 publications
0
12
0
Order By: Relevance
“…Similar to previous research, the results of this study showed that participants relied on local reference frames rather than global reference frames or orientation-free representations. Other studies conducted in virtual environments also found no advantages of global landmarks on learning (Credé 2019 ). In another experiment, participants navigated four virtual environments with different landmark conditions: only global landmarks, only local landmarks, global and local landmarks and no landmark conditions (Gardony et al 2011 ).…”
Section: Visibility Of Landmarksmentioning
confidence: 88%
“…Similar to previous research, the results of this study showed that participants relied on local reference frames rather than global reference frames or orientation-free representations. Other studies conducted in virtual environments also found no advantages of global landmarks on learning (Credé 2019 ). In another experiment, participants navigated four virtual environments with different landmark conditions: only global landmarks, only local landmarks, global and local landmarks and no landmark conditions (Gardony et al 2011 ).…”
Section: Visibility Of Landmarksmentioning
confidence: 88%
“…Arousal related to an affective response has also been shown to impact how navigators process or learn an environment. During learning, when presented with a stressor (time pressure), individuals learned local landmarks (only one building present at a time) more accurately than global landmarks (multiple high-rise skyscrapers visible simultaneously; Credé, Thrash, Hölscher, & Fabrikant, 2019 ). This suggests that, when aroused, people rely more heavily on landmarks than landmark configurations.…”
Section: Introductionmentioning
confidence: 99%
“…Years of spatial cognition and navigation research point to vast individual differences in navigational abilities Montello, 1998;Weisberg & Newcombe, 2018) and situational strategies (e.g., navigating under stress; Credé et al, 2019;Frei et al 2016;Gagnon et al, 2018;Ruginski et al, 2018). Designing navigation systems that take into account and adapt to these individual abilities, preferences, and contexts remains a challenge.…”
Section: Adjusting For Contextmentioning
confidence: 99%